2017
DOI: 10.1186/s13052-017-0389-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an educational program on recognition, treatment and report of child abuse

Abstract: BackgroundPediatricians play a crucial role in the identification and management of child abuse and neglect (CAN) but they often don’t have a formal specialized training.MethodsWe analysed retrospectively data about patients, 0 - 18 years of age, victims of CAN between 1 April 2005 and 30 April 2015. The aim of the study was to evaluate the effect of a multidisciplinary educational program, “CAN: prevention strategies, individuation and treatment”, on the knowledge, case recognition, treatment and follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…20,21 Education on sexuality using an appropriate methodology is even important for young children, and the combined work of parents, teachers, and health professionals can help to prevent sexual assault and domestic violence. 22 A notable finding of the present study is that $ 10% of the teenagers reported sexual initiation when < 13 years old. This suggests vulnerability to sexual violence, because children at this age cannot distinguish sexual abuse from deliberate and consensual sexual relations.…”
Section: Discussionsupporting
confidence: 47%
“…20,21 Education on sexuality using an appropriate methodology is even important for young children, and the combined work of parents, teachers, and health professionals can help to prevent sexual assault and domestic violence. 22 A notable finding of the present study is that $ 10% of the teenagers reported sexual initiation when < 13 years old. This suggests vulnerability to sexual violence, because children at this age cannot distinguish sexual abuse from deliberate and consensual sexual relations.…”
Section: Discussionsupporting
confidence: 47%
“…Finally, in the absence of a pediatric Observation Unit, the patient would be hospitalized in ordinary wards to perform "clinical observation". This leads to considerably higher costs and bed occupancy, which could be used for cases with higher indications of hospitalization [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Current child protection laws require medical providers among other professionals to report any case of suspected abuse to CYPS. Despite the pivotal role of physicians in accurately identifying and reporting cases with suspected abuse, some physicians receive minimal training to identify and report cases of abuse [ 4 , 18 21 ]. Levi and Brown reported a significant variability among pediatricians' level of interpreting and understanding of reasonable suspicion for abuse [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferrara et al discussed the impact of a pilot training program for physicians in Italy to help them identify and report cases of child maltreatment. The authors found that training pediatricians on the use of objective signs to supplement their clinical judgment helped to accurately identify more cases of abuse [ 18 ]. Orthopaedic surgeons are at the forefront of evaluating and documenting evidence for suspected child abuse because about 28% of confirmed child abuse cases involve one or more fractures [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%